Pengaruh Keberagaman Gender dan Corporate Social Responsibility terhadap Manajemen Laba - Anggarayni, Suci; Wenny, Cherrya Dhia (Universitas Multi Data Palembang, 2024)
This research aims to examine the effect of Gender Diversity and Corporate Social Responsibility to earn management in non – cyclicals consumer sectors listed on the IDX in 2019-2022. Sample collection using purposive sampling technique so as to get 36 sample companies. The data analysis technique uses multiple linear regression tests. The results showed that Gender Diversity has no significant effect to earn management, beside CSR has significant effect to earn management.